2014
DOI: 10.1111/apa.12760
|View full text |Cite
|
Sign up to set email alerts
|

Blood sugar levels are higher in obese young children in Sweden than in Poland

Abstract: Swedish obese young children had higher glucose levels than Polish obese young children. This suggests that Swedish obese children face a higher risk of the prediabetic stage impaired fasting glycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The findings in Sweden were different from the other countries in that there was a more marked increase of both LDL‐ and HDL‐cholesterol in the intervention than in the control regions. A significantly higher level of fasting glucose in Swedish children has also been observed previously in two studies comparing obese Swedish and Polish or obese Swedish and German children . Several explanations not related to insulin resistance were suggested for these findings, such as differences in genetic traits, in levels of vitamin D or exposure to viral infections .…”
Section: Discussionsupporting
confidence: 83%
“…The findings in Sweden were different from the other countries in that there was a more marked increase of both LDL‐ and HDL‐cholesterol in the intervention than in the control regions. A significantly higher level of fasting glucose in Swedish children has also been observed previously in two studies comparing obese Swedish and Polish or obese Swedish and German children . Several explanations not related to insulin resistance were suggested for these findings, such as differences in genetic traits, in levels of vitamin D or exposure to viral infections .…”
Section: Discussionsupporting
confidence: 83%
“…Hagman et al in her studies pointed out those regional differences in glucose levels exist. A study that compared the plasma glucose level between Swedish and Polish children concluded that obese Swedish children have higher glucose levels in comparison to obese children from Poland [ 53 ]. Also, the risk of having impaired plasma glucose is higher in obese children from Sweden compared to obese children in Germany [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“… 26 However, these results are probably not contradictory as we have previously shown that obese children in general have elevated fasting glucose levels compared with normal weight children. 12 It is therefore possible that obesity and overweight contribute to the observed difference in T2DM risk observed in the population-based study of fasting glucose and future T2DM risk. 26 Indeed, in the present study, we observed an 18.5 times higher risk for T2DM medication collection among obese children and adolescents with NFG than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 However, IFG is also prevalent in pre-pubertal obese children. 12 Factors shown to affect the risk for IFG in the obese young population include gender, age and degree of obesity. 9 …”
Section: Introductionmentioning
confidence: 99%